The biographical-narrative research in Education: A research approach co-constructed from subjectivities, from the fabric of multiple realities - Benjamín Barón; Juan Simón Cancino (Corporación Universitaria Minuto de Dios, 2014)
The article presents the biographical - narrative focus of research that was implemented in the investigative process that sought the understanding of the discriminatory forms engrained in verbal communication, regarding teacher-student relationship, generated and exemplified in the life condition of the person in cases of afro-descendant identity and the physically challenged ones, developed in the macro political formation and citizenship at school: pedagogical, ethical-moral and the political views of La Salle University. The concepts that emerge in the proposal of this approach (discrimination and recognition of the other) construct the meaning from a great array of realities in which the implied subjects are immersed in the development and production of this significant knowledge.